Productivity enhancement of sweet corn (Zea mays) through organic weed management practices - CHOUDHARY, ROSHAN; VERMA, ARVIND; SHARMA, S K; YADAV, S K; JAIN, R K; JAT, GAJANAND; CHOUDHARY, R S; JAIN, DEVENDRA (The Indian Journal of Agricultural Sciences, 2021)
Area under organic cultivation of crops is increasing not only in India but also in Rajasthan as well. Weeds are often recognized as the most serious threat to organic crop production and fear of ineffective weed control is often perceived by farmers as one of the major obstacles to conversion from conventional to organic farming. A two years field experiment was conducted to study the non-chemical methods of weed management in organically grown sweet corn (Zea mays L.) during 2018-19. Among the 12 organic weed management treatments, soil solarization + plastic mulch at sowing resulted in significantly lower weed density, weed dry matter, higher yield attributes and yield over other treatments but at par with stale seed bed preparation + plastic mulch at sowing during both the years. Stale seed bed preparation + plastic mulch at sowing gave highest net returns and benefit-cost ratio of ₹ 62746 and 105201 and 1.62 and 2.35, respectively followed by weedy check, which gave the net returns and benefit: cost ratio of ₹ 16093, 26858 and 0.96 and 2.18, respectively.